Understanding cardiac troponin biology: all other cardiac biomarkers shall rest in peace? - Lippi, Giuseppe; Plebani, Mario (Journal of Laboratory and Precision Medicine, 2019)
The concept that high-sensitivity cardiac troponin immunoassays outperform creatine kinase MB (CK-MB) and myoglobin in the diagnostics of acute coronary syndrome has been put forward more than 10 years ago, and is now virtually incontestable. In the seminal study of Keller et al. (1), cardiac troponins, myoglobin and CK-MB were measured in over 1,800 consecutive patients admitted with suspected acute myocardial infarction. In all patients, the diagnostic performance (area under the curve, AUC) of both high-sensitivity cardiac troponin I (cTnI) (AUC, 0.96) and high-sensitivity cardiac troponin T (AUC, 0.85) was found to higher than that of both myoglobin (AUC, 0.82) and CK-MB (AUC, 0.73). Even more importantly, the early (i.e.,